Changement Climatique Et Paludisme En Côte d’Ivoire : Représentations Sociales Et Connaissance Des Populations d’Adjéyaokro (Bouaké) - Mazou Gnazegbo Hilaire (European Scientific Journal, ESJ, 2017)
Climate change characterized by increasing average daily temperature and changing seasons has become a public health concern, with the incidence of malaria in recent years. Despite research on global warming and efforts to fight malaria (sensitization campaigns, distribution of insecticide-treated nets, care of the sick), the excessive heat continues to do damage. What is the link between climate change and malaria? What are people's perceptions of climate change in relation to malaria? To address these concerns, the survey on the impact of climate change on malaria was conducted through in-depth interviews with some 20 people from the village of Adjéyaokro in Bouaké. It is mainly the result of our investigations that the populations do not link the effects of climate change and the risk of exposure to malaria.